Chimeric Peptides/Proteins Encoded by circRNA: An Update on Mechanisms and Functions in Human Cancers - Khan, Faiz Ali; Nsengimana, Bernard; Khan, Nazeer Hussain; Song, Zhenhua; Ngowi, Ebenezeri Erasto; Wang, Yunyun; Zhang, Weijuan; Ji, Shaoping (Frontiers in Oncology, 2022)
Recently, the discovery of circular RNAs (circRNAs) is considered the big breakthrough in cell bio-sciences. Owing to their unique characteristics of being highly conserved, relatively longer half-life, and involvement in RNA maturation, transportation, epigenetic regulation, and transcription of genes, circRNAs have attained the attention of researchers across the globe. The critical importance of these circRNAs is due to the presence of small open reading frames (ORFs) that enable them to encode proteins. Over the years of research from last decade, it has been well established that these encoded proteins moderate essential cellular activities such as ubiquitination, degradation, proliferation, c-Myc oncoprotein stabilization, invasion, epithelial-mesenchymal transition (EMT), apoptosis, and autophagy and have developed an association with the development and progression of cancers by modulating diverse signaling pathways. In cancer biology, these peptides have potential role as biomarkers for the prognosis of cancer and are being used as drug targets against tumorigenesis. Considering their critical role in modulating cellular events and importance in the war against cancer, in the present review, we thoroughly discussed the biogenesis of circRNAs and their functional mechanisms along with a special emphasis on the recently reported chimeric peptides encoded by spanning the back-splice junction of circRNAs. Additionally, this review summarises the current state of knowledge and future consensus about the use of circRNAs in cancer clinics.